Protocols for high-risk pregnancies : an evidence-based approach - Queenan, John T.; Spong, Catherine Y.; Lockwood, Charles J. (Chichester, West Sussex ; Hoboken, NJ : Wiley Blackwell, 2015)
High-risk pregnancies present life-threatening challenges to two of your patients: the mother and her fetus. The direct, exemplary guidance in Protocols for High-Risk Pregnancy enables you to -better understand your patients' conditions -devise optimum management strategies -maximize the outcome and minimize the complications for both the mother and her fetus To enhance clinical relevance, each protocol is written as if the patient were present. Evidence to support an intervention is given where it exists. The authors' experience provides additional wise counsel. Key references provide the springboard for a deeper understanding of a topic. In this more compact and fully updated sixth edition, new protocols include -Amniotic fluid disorders -Depression -Fetal growth restriction -HIV -Indicated late preterm and early term birth -Malaria -Noninvasive prenatal diagnosis Designed for clinical practice by the leaders of two generations of maternal-fetal medicine, no obstetrician or obstetric health care provider can afford to miss Protocols for High-Risk Pregnancy.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Pregnancy -- Complications; Pregnant women -- Medical care; Evidence-based medicine; Pregnancy Complications; Pregnancy, High-Risk.; Evidence-Based Medicine; Medical; MEDICAL -- Gynecology & Obstetrics; Evidence-based medicine; Pregnancy -- Complications; Pregnant women -- Medical care; Electronic books